2015
DOI: 10.1371/journal.pone.0145665
|View full text |Cite
|
Sign up to set email alerts
|

Major Quantitative Trait Loci and Putative Candidate Genes for Powdery Mildew Resistance and Fruit-Related Traits Revealed by an Intraspecific Genetic Map for Watermelon (Citrullus lanatus var. lanatus)

Abstract: An intraspecific genetic map for watermelon was constructed using an F2 population derived from ‘Arka Manik’ × ‘TS34’ and transcript sequence variants and quantitative trait loci (QTL) for resistance to powdery mildew (PMR), seed size (SS), and fruit shape (FS) were analyzed. The map consists of 14 linkage groups (LGs) defined by 174 cleaved amplified polymorphic sequences (CAPS), 2 derived-cleaved amplified polymorphic sequence markers, 20 sequence-characterized amplified regions, and 8 expressed sequence tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
(65 reference statements)
4
43
0
Order By: Relevance
“…In addition to Arabidopsis , NBS-LRR proteins have been found in powdery mildew resistance-associated regions in watermelon, a relative of Cucurbita spp. in the Cucurbitaceae family [7174]. In addition to the putative NBS-LRR locus, numerous other candidates exist in the interval.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Arabidopsis , NBS-LRR proteins have been found in powdery mildew resistance-associated regions in watermelon, a relative of Cucurbita spp. in the Cucurbitaceae family [7174]. In addition to the putative NBS-LRR locus, numerous other candidates exist in the interval.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kim et al . () identified a major QTL ( pmr2 . 1 ) for resistance to powdery mildew race 1W on chromosome 2 that explained 80.0% of the phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, two distinct powdery mildew races, 1W and 2W, are known for watermelon, and several cultivars and wild species highly resistant to these races have been identified (Davis et al, 2007;Tetteh et al, 2010). Recently, Kim et al (2015) identified a major QTL (pmr2.1) for resistance to powdery mildew race 1W on chromosome 2 that explained 80.0% of the phenotypic variation. In the present study, GWAS analysis identified a major peak associated with powdery mildew race 2W resistance also on chromosome 2 (~29.2-31.0 Mb) overlapping with QTL pmr2.1, and additional SNPs on chromosomes 3, 6, 8, 9 and 10 associated with race 2W resistance (Figure 4b and Table S12).…”
Section: Discussionmentioning
confidence: 99%
“…For fruit shape, two CAPS markers SUN -Cla011257 and wsb3 -24 reported by Kim et al (2015c) were examined ( Table 1).…”
Section: Marker Genotyping For Fruit -Related Traitsmentioning
confidence: 99%
“…Based on bulked segregant analysis (BSA), Kim et al (2015b) demonstrated that a sequence characterized amplified region (SCAR) marker (wsb6 -11) is tightly linked to the stripe pattern observed in the JT cultivar, which is useful for discriminating this cultivar from CT and non -striped rind types. By constructing an intraspecific genetic map and performing quantitative trait locus (QTL) analysis, Kim et al (2015c) identified two cleaved amplified polymorphic sequence (CAPS) markers, SUN -Cla011257 and wsb3 -24, for fruit shape. For fruit flesh color, Bang et al (2007) developed a CAPS (Lcyb) and a SCAR (Clcyb.600) marker from the Lycopene βcyclase (Lcyb)gene, distinguishing red and canary yellow -fleshed fruit.…”
Section: Introductionmentioning
confidence: 99%